The Implementation of Learning Based on Islamic Wasathiyah Values to Build Student Character at SMKN 1 Salam: Implementasi Pembelajaran Berbasis Nilai Wasathiyah Islam untuk Membangun Karakter Siswa di SMKN 1 Salam - Cahyaningsih, Tri; Ridhani, Akhmad Rizkhi; Dzukriyah, Silfa; Futuna, Jazilatul (Yayasan Pendidikan Islam (YPI) AN NUR INSANI, 2025)
This study aims to describe learning methods, evaluation strategies, and assessment models that integrate Islamic wasathiyah values at SMKN 1 Salam. The diverse ethnic and religious backgrounds of students present a challenge in designing inclusive and tolerant learning experiences rooted in moderate Islamic principles. Using a literature review and case study approach, the findings indicate that Project-Based Learning (PjBL), Problem-Based Learning (PBL), and Teaching Factory (TeFa) are effective in character development. The use of formative and self-reflective assessments is recommended to evaluate students' understanding and application of wasathiyah values.